An Aqueous Redox‐Flow Battery with High Capacity and Power: The TEMPTMA/MV System. Issue 46 (18th October 2016) - Janoschka, Tobias; Martin, Norbert; Hager, Martin D.; Schubert, Ulrich S.
Abstract: Redox‐flow batteries (RFB) can easily store large amounts of electric energy and thereby mitigate the fluctuating output of renewable power plants. They are widely discussed as energy‐storage solutions for wind and solar farms to improve the stability of the electrical grid. Most common RFB concepts are based on strongly acidic metal‐salt solutions or poorly performing organics. Herein we present a battery which employs the highly soluble N, N, N ‐2, 2, 6, 6‐heptamethylpiperidinyl oxy‐4‐ammonium chloride (TEMPTMA) and the viologen derivative N, N ′‐dimethyl‐4, 4‐bipyridinium dichloride (MV) in a simple and safe aqueous solution as redox‐active materials. The resulting battery using these electrolyte solutions has capacities of 54 Ah L −1, giving a total energy density of 38 Wh L −1 at a cell voltage of 1.4 V. With peak current densities of up to 200 mA cm −2 the TEMPTMA/MV system is a suitable candidate for compact high‐capacity and high‐power applications. Abstract : Tempting solutions : Redox‐flow batteries (RFB) are widely considered as energy‐storage solutions for wind generators and solar farms. A highly soluble, organic material system for aqueous RFBs is found to be N, N, N ‐2, 2, 6, 6‐heptamethyl piperidinyl oxy‐4‐ammonium chloride (TEMPTMA) and N, N ′‐dimethyl‐4, 4‐bipyridinium dichloride (MV). It has capacities of over 54 Ah L −1 (ca. 38 Wh L −1 ), a cell voltage of 1.4 V, and peak current densities of up to 200 mA cm −2 .